The effect of red pomegranate provision on malondialdehyde and blood lactic acid level in rats with maximum physical activity - Zainuddin, Ahmad; Susanto, Hardhono; Rosidi, Ali (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2019)
The primary objective of this research was to examine the effect of provision of red pomegranate juice on the levels of malondialdehyde (MDA) and blood lactic acid in Wistar rats with maximum physical activity. The study employed a true experiment design. The pretest-posttest with control group design was done on 35 rats given maximum physical activity and treatment for 28 days. The rats were divided into 5 groups: the control group, group with treatment of multivitamin, group with treatment of red pomegranate 2 ml, 4 ml, and 6 ml. The MDA level was measured by TBARS method and lactic acid levels were analysed using ELISA. Comparison statistical analysis was done using paired t-test, while comparison of mean differences between treatment groups were tested using One-way ANOVA, and followed by LSD as the post hoc test. Provision of red pomegranate juice in a variety of doses significantly decreased the levels of MDA and blood lactic acid (p<0.05). The highest MDA level decrease occurred in the group treated with multivitamin (68.02%) and the highest decrease in the levels of blood lactic acid occurred in the group with 6 ml red pomegranate juice (25.94%). Based on the findings, it can be concluded that red pomegranate juice can lower the levels of MDA and blood lactic acid significantly in rats with maximum physical activity.